Stable carbon and nitrogen isotope variations in canine dentine growth layers of Kerguelen southern elephant seals - Martin, Céline; Bentaleb, Ilham; Steelands, Stéphanie; Guinet, Christophe (Marine Ecology Progress Series, 2011)
International audience Foraging behaviour of mammals, namely the change in distribution and trophic levels from juvenile stage to adulthood, can be investigated by measuring δ13C and δ15N stable isotopes for layers deposited in a growing tooth. For the first time, we describe geographic differences in the ontogeny of foraging strategies and in the niche partitioning process according to sex and age of a highly sexually dimorphic species: the southern elephant seal Mirounga leonina. Canines from 8 males and 6 females were analysed for δ13C and δ15N stable isotope signatures. To assess intra-individual variability, instead of analysing collagen we analysed the bulk dentine within each of the 4 growth layers deposited annually. The δ13C signature revealed that, in individuals of 1 to 4 yr of age, teeth of both males and females exhibited large intra-individual variation in δ13C, suggesting that juveniles were foraging over a broad range of marine habitats encompassing both sub-Antarctic and Antarctic waters. Four out of the 6 teeth taken from females were collected on individuals younger than 4 yr, preventing investigation of longer-term changes. A δ13C pattern emerged for males older than 4 yr: individuals became resident to either a sub- Antarctic (-17‰) or an Antarctic (-20‰, both values reported as deviations from the Vienna PeeDee Belemnite standard) foraging habitat, with a decrease in intra-individual variability. Up to the age of 4 yr, juvenile males were at a slightly higher trophic level than juvenile females, but by the age of 4 yr, while their δ13C signature revealed that they were faithful to their foraging habitat, males exhibited a significant increase in their trophic levels, as shown by their δ15N signature.